Structure–Activity Relationship Studies of SARS-CoV‑2 Main Protease Inhibitors Containing 4‑Fluorobenzothiazole-2-carbonyl Moieties - Tsuji, Kohei; Ishii, Takahiro; Kobayakawa, Takuya; Higashi-Kuwata, Nobuyo; Shinohara, Kouki; Azuma, Chika; Miura, Yutaro; Nakano, Hiroki; Wada, Naoya; Hattori, Shin-ichiro; Bulut, Haydar; Mitsuya, Hiroaki; et al. (Journal of medicinal chemistry, 2023)
The main protease (Mpro) of SARS-CoV-2 is an attractive target for the development of drugs to treat COVID-19. Here, we report the design, synthesis, and structure–activity relationship (SAR) studies of highly potent SARS-CoV-2 Mpro inhibitors including TKB245 (5)/TKB248 (6). Since we have previously developed Mpro inhibitors (3) and (4), several hybrid molecules of these previous compounds combined with nirmatrelvir (1) were designed and synthesized. Compounds such as TKB245 (5) and TKB248 (6), containing a 4-fluorobenzothiazole moiety at the P1′ site, are highly effective in the blockade of SARS-CoV-2 replication in VeroE6 cells. Replacement of the P1–P2 amide with the thioamide surrogate in TKB248 (6) improved its PK profile in mice compared to that of TKB245 (5). A new diversity-oriented synthetic route to TKB245 (5) derivatives was also developed. The results of the SAR studies suggest that TKB245 (5) and TKB248 (6) are useful lead compounds for the further development of Mpro inhibitors.